PENGARUH KEGIATAN SUPERVISI KEPALA SEKOLAH TERHADAP KEMAMPUAN MENGAJAR GURU DI SEKOLAH SMA NURUL HASANAH - Nurjannah, Herdi Ramon, Arief Bagus Setia, Mhd Zulkifli Hasibuan, (FKIP UMN ALWASHLIYAH, 2025)
In the perspective of globalization, regional autonomy, and decentralization of education and to make school-based management and competency-based curriculum a success, the principal is a central figure who must be a role model for other education personnel in the school. Therefore, to support the success of the changes made and expected, it is necessary to prepare professional principals who are willing and able to plan, implement, and evaluate various policies and changes made effectively and efficiently. Supervision can actually be carried out by the principal who acts as a supervisor, but in the modern education organization system, a special supervisor is needed who is more independent and can increase objectivity in coaching and carrying out his duties. If supervision is carried out by the principal, then he must be able to carry out various supervisions and controls to improve the performance of education personnel. Supervision and control are also preventive measures to prevent education personnel from committing deviations and to be more careful in carrying out their work. Supervision and control carried out by the principal on his education personnel, especially teachers, is called clinical supervision, which aims to improve the professional abilities of teachers and improve the quality of learning through effective learning.